Acilación quimioselectiva de hidroxialcanotioles catalizada por lipasas en medio orgánico - Iglesias, Luis Emilio (1996)
Various bi- and polifunctional hydroxyalkanethiols were chemospecificallyacylated to O-acylesters by lipase-catalyzed transesterifications in organic media. Inaddition, hydroxyalkanethiols with two hydroxyl groups exhibited regiospecificity orregioselectivity, depending on the nature of both the substrate and the lipase. As the chainlength of the α,ω-hydroxyalkanethiol increased, the reaction was limited to smaller acylmoieties. Experimental conditions under which enzymatic acylations were carried out andtheir results are presented and discussed. Biocatalyzed transesterifications allowed thepreparation of twenty-four new esters. The preparation of some α,ω-hydroxyalkanethiolsand the mass spectra of substrates and products are also presented and discussed.